Strength training improves exercise economy in triathletes during a simulated triathlon - Luckin-Baldwin, K. M.; Badenhorst, C. E.; Cripps, A. J.; Landers, G. J.; Merrells, R. J.; Bulsara, M. K.; Hoyne, G. F. (International Journal of Sports Physiology and Performance, 2021)
Purpose: The completion of concurrent strength and endurance training can improve exercise economy in cyclists and runners; however, the efficacy of strength training (ST) implementation to improve economy in long-distance (LD) triathletes has not yet been investigated. The purpose of this study was to investigate physiological outcomes in LD triathletes when ST was completed concurrently to endurance training.